2010 International Conference on Simulation of Semiconductor Processes and Devices 2010
DOI: 10.1109/sispad.2010.5604517
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modeling hysteresis and resistive switching in bipolar oxide-based memory

Abstract: We have developed a stochastic model of the resistive switching mechanism in resistive random access memory (RRAM) based on electron hopping. The distribution of electron occupation probabilities obtained with our approach is in good agreement with previous work. In particular, a low occupation region is formed near the cathode for bipolar switching behavior or near the anode for unipolar switching behavior. This result indicates that a decrease of the switching time with increasing temperature cannot be expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Perpendicular cells with an interface-induced anisotropy show potential, but still require a reduction of damping and an increase of thermal stability [17]. The in-plane MTJs exhibit a high thermal stability, but still require a reduction of the critical current density [17].…”
Section: Spintronic Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…Perpendicular cells with an interface-induced anisotropy show potential, but still require a reduction of damping and an increase of thermal stability [17]. The in-plane MTJs exhibit a high thermal stability, but still require a reduction of the critical current density [17].…”
Section: Spintronic Memorymentioning
confidence: 99%
“…The simulations show that, while preserving all the advantages of the first generation structure, such as fast switching, high thermal stability factor, and very narrow distribution of switching times, the second generation of the free layer can be easier fabricated and offers a higher potential for STT-MRAM performance optimization. A very narrow distribution of switching times of composite structures is useful not only for application in an STT-MRAM memory cell, but also for magnetic sensors [17].…”
Section: Spintronic Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…This switching behavior leads to a decrease of the switching energy barrier, while preserving the thermal stability. The reduction of the switching time depending on geometry parameters is investigated in (31), (32). It is shown that a structure with a recording layer composed of ellipses with the axes a/2 and b inscribed into a rectangle a > b is characterized by a switching time similar to the one in a previously considered structure with a composite recording layer, without sacrificing thermal stability.…”
Section: Spin Transfer Torque Magnetic Random Access Memorymentioning
confidence: 99%